2020
DOI: 10.15408/sjsbs.v7i4.15068
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Corporate Social Responsibility sebagai Variabel Moderating

Abstract: The role of Corporate Social Responsibility (CSR) as a moderating variable in the effect of probability, leverage, and size of the company, on the company values listed on the Stock Exchange from 2015 through 2018 is examined in this study. The target population consists of 96 companies and 51 of them are considered as the sample according to a pool sampling method. Moderate Regression Analysis (MRA) is considered as the main method to identify and describe the relationship between the variables. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 0 publications
5
17
0
2
Order By: Relevance
“…The greater the value of ISR reporting, the greater the impact on increasing the company's value. The findings of this study are also consistent with previous research that shows leverage has no effect on firm value (Agustina, 2020;Chen & Lee, 2017;Chung et al, 2018;Hussain et al, 2021;Jihadi et al, 2021;Khoiriyah R, 2020;Nuansari et al, 2020;Riniyati, 2019;Susanti & Pertiwi, 2019).…”
Section: Structural Model Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The greater the value of ISR reporting, the greater the impact on increasing the company's value. The findings of this study are also consistent with previous research that shows leverage has no effect on firm value (Agustina, 2020;Chen & Lee, 2017;Chung et al, 2018;Hussain et al, 2021;Jihadi et al, 2021;Khoiriyah R, 2020;Nuansari et al, 2020;Riniyati, 2019;Susanti & Pertiwi, 2019).…”
Section: Structural Model Analysissupporting
confidence: 92%
“…Then, (Othman et al, 2009) refined the framework by adding a disclosure theme, namely the theme of Corporate Governance. It has been shown that ISR reporting has a positive and significant effect on firm value (Agustina, 2020;Chen & Lee, 2017;Chung et al, 2018;Hussain et al, 2021;Jihadi et al, 2021;Khoiriyah R, 2020;Nuansari et al, 2020;Riniyati, 2019;Susanti & Pertiwi, 2019) More extensive and transparent ISR reporting will be carried out by companies with high profitability compared to those with low profitability (Othman et al, 2009in Husain et al, 2021. M.Yusuf1 dan Nurul Shayida2, 2020; Putra & Aisyah, 2022;Mayasari et al, 2022;) all find that profitability has a positive and significant effect on ISR reporting.…”
Section: Islamic Social Reporting (Isr)mentioning
confidence: 99%
“…Increased profitability will help investors to see the good performance of the company it will have an impact on increasing firm value. This is evident from the research results pinpointing that profitability has a positive and significant effect on firm value (Fadhilah, et al, 2021;Obradovich & Gill , 2012;Tarihoran, et al, 2019;Rahmadhani & Anwar, 2021;Karina & Evendi, 2019;Rusnaeni, et al, 2022;Sitompul, 2019;Nuansari, et al, 2020;Chabachib, et al, 2020;and Anjarwati, et al, 2016), as well as research that highlighted that profitability has a significant effect on firm value (Meze and Tohari, 2020;Astutik, 2021;Mardi, Hermanto & Widiastuty, 2019;Angary, Handojo, & Supriatna, 2020;Markonah , et al, 2020;and Frederica, 2019). This is despite a few results denoting that profitability does not affect firm value (Nazir & Agustina, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…Berdasarkan Hasil beberapa penelitian yang dilakukan oleh Pertiwi and Chusnah (2020), Nuansari et al (2020), Dewi et al (2019, Pradita and Suryono (2018) didapatkan bahwa Corporate Social Responsibility mampu memoderasi dan memperkuat pengaruh profitabilitas terhadap nilai perusahaan. Hal tersebut sejalan dengan teori legitimasi, yang berpedoman bahwa setiap perusahaan harus mampu menjalankan dan mengelola usahanya dengan berorientasi pada para pemangku kepentingan (society) (Gray et al, 1996) Likuiditas adalah bagaimana perusahaan mampu menutup atau melunasi kewajiban jangka pendek yang dimiliki dengan jaminan aset lancar perusahaan (Hartono et al, 2018).…”
Section: Hipotesis Penelitianunclassified
“…Dapat diambil kesimpulan, secara statistik pada tingkat kepercayaan 95 persen Leverage tidak berpengaruh signifikan terhadap Nilai Perusahaan. Hasil pengujian hipotesis tersebut, sependapat dengan penelitian yang dilakukan oleh Chusnah et al (2020), Nuansari et al (2020), dan Putra et al (2017) menyatakan bahwa leverage yang di proksikan dengan Debt to Equity Ratio (DER) tidak berpengaruh signifikan terhadap nilai perusahaan.…”
Section: Leverage Berpengaruh Positif Terhadap Nilai Perusahaanunclassified